Antigen peptide transporter 1 is involved in the development of fructose‐induced hepatic steatosis in mice. Issue 8 (22nd July 2013) - Arindkar, Shailendra; Bhattacharjee, Jashdeep; Kumar, Jerald Mahesh; Das, Barun; Upadhyay, Pramod; Asif, Shajahan; Juyal, Ramesh C; Majumdar, Subeer S; Perumal, Nagarajan
Abstract: Background and Aim: The purpose of this study is to assess whether the decrease in CD8 cells has any role in the development of non‐alcoholic fatty liver disease (NAFLD). In this study, we therefore used antigen peptide transporter 1 (TAP1 −/− ) mice that cannot transport major histocompatibility complex class I antigens onto the cell surface resulting in failure of the generation of CD8 cells. Methods: Wild‐type C57Bl/6J and TAP1 −/− mice were fed with 30% fructose solution for 8 weeks. The percentage of CD4, CD8 cells in peripheral blood mononuclear cells, and liver were sorted by fluorescence‐activated cell sorting in both control and fructose‐treated mice. Bodyweight, histopathological changes, oil red O staining, glucose tolerance test, intraperitoneal insulin tolerance test, serum levels of triglycerides, cholesterol, aspartate aminotransferase, and alanine aminotransferase were also evaluated. Quantitative real‐time polymerase chain reaction was performed to determine the expression of specific genes involved in development of fatty changes in the liver. Results: Chronic consumption of fructose in TAP1 −/− mice did not develop NAFLD, insulin resistance, or change in level of CD8 cells. Moreover, there was delay in relative expression levels of genes involved in development of NAFLD in fructose‐treated TAP1 −/− mice. Conclusion: Taken together, the data suggest that TAP1 −/− ‐deficient mice displayed reduced levels of CD8 cells that have a vital role in the initiation and propagation of liver inflammation and is a casual role in the beginning of fructose‐induced liver damage as well as insulin resistance in mice.